CAPACITY BUILDING PROJECT : PEMBUATAN PRESENTASI VIRTUAL UNTUK MENINGKATKAN LITERASI DIGITAL BAGI GURU DI YAYASAN PENDIDIKAN SUBULUSSALAM - Zulaikah, Zulaikah; Mustofa, M. Iqbal; Agustina, Eka; Arif, Fat’ul (Jurnal Abdi Insani, 2024)
A professional teacher is one of the key components in determining quality education, where an individual must meet the educator qualification standards with four essential competencies. These competencies include the teacher's ability to manage learning or pedagogical competence, which requires teachers to have the skills to make learning more engaging. Next, there is the professional competence, which also requires teachers to develop the material they master creatively, especially in terms of using technology. The aim of this activity is to enhance teachers' digital literacy to address the paradigm shift in education triggered by the advancement of information and communication technology. The method used involves providing training to teachers and hands-on practice using virtual presentation applications. As a result, teachers acquire the skills and knowledge needed to become more effective and productive users of technology in their teaching practices, leading to improved learning quality and responding to the increasingly complex demands of the future. Moreover, virtual presentations not only make it easier for teachers to explain lessons but also stimulate discussions among students to explore their knowledge more deeply. This greatly facilitates both teacher-student interaction, extending beyond the classroom, while also allowing teachers to directly apply these skills in their teaching, thus enhancing student engagement and understanding.